KONSTRUKSIVISME SEBAGAI PARADIGMA PSIKOLOGIS DALAM PROSES BELAJAR - Muhammad Zakki Fuad; Nur Halimatus Sa’diyah; Bayu Amrullah, M. Kholid; Bayu Amrullah, M. Yunus Abu Bakar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This article eamines constuctivism, a psychological paradigm that plays an important role in explaining the human learning process. Using a descriptive-qualitative approach, this study reviews literature discussing constructivism theory. The study reveals that constructivism has given rise to innovative, learner-centered learning models that encourage active engagement and emphasize understanding over memorization. Thus, constructivism functions not only as a theoretical framework but also as a practical foundation for transforming learning in the 21st century.